Blackbox Challenge in Software Teaching and Learning - Anand Jeyaraj; Vikram Sethi (Letters in Information Technology Education (LITE), 2025)
The rapid proliferation and integration of artificial intelligence (AI) capabilities within information systems (IS) tools have significantly reshaped how individuals approach and perform tasks. This evolution necessitates a critical examination of the emerging “black box challenge” a phenomenon in which the internal mechanisms and complexities of AI-driven functionalities are obscured from users, even as these tools facilitate efficient task completion. One salient characteristic of many AI-powered tools such as pattern recognition contributes to this opacity by abstracting away cognitive processes traditionally required for problem-solving. For instance, Microsoft Excel's Flash Fill feature exemplifies how students can rapidly achieve accurate outputs without necessarily engaging with underlying logic or methodological reasoning. While such tools undoubtedly offer productivity gains, their widespread use may unintentionally diminish opportunities for learners to develop essential cognitive competencies. Consequently, the reliance on AI-driven automation in educational contexts raises profound pedagogical concerns. Over time, the erosion of critical thinking, problem-solving abilities, and metacognitive engagement may compromise not only individual intellectual growth but also the broader societal capacity for innovation and informed decision-making. Thus, the unchecked normalization of such technologies in learning environments may inadvertently undercut the very foundations of lifelong learning and democratic vitality